Pengelolaan Keuangan Usaha Mikro dalam Menjaga Keberlanjutan Usaha: Studi Kasus Toko Serba Tiga Lima di Ambarawa - Zalukhu, Desmeni; Maria Th, Aletta Dewi (Mahesa Research Center, 2026)
This article aims to describe and analyze micro-enterprise financial management in maintaining the business sustainability of Toko Serba Tiga Lima in Ambarawa, Semarang Regency. The problem focuses on financial management practices, including financial planning, record keeping, financial control, and financial evaluation, as well as their role in supporting business sustainability amid limited capital and increasing competition. To address this issue, the study employs theoretical perspectives on micro-enterprise financial management and business sustainability. Data were collected through interviews, observations, and documentation and were analyzed qualitatively. The results indicate that financial management practices remain simple, unstructured, and unsupported by consistent financial records and a clear separation between business and personal finances. Nevertheless, simple cash flow management and routine expenditure control play an important role in maintaining operational sustainability. This study concludes that strengthening more systematic financial management is essential for micro-enterprises not only to survive but also to enhance their potential for sustainable growth, while providing practical contributions to the development of micro-enterprise financial management at the local level.